Ketahanan Ekologi Sosial dan Sistem Komunikasi Pembangunan Desa Wisata - Satriya, Candra Yudha; Triyono, Agus; Indrayani, Heni (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2025)
This study examines the socio-ecological crisis in Wanurejo Village following its transformation into a tourism destination. From a constructivist perspective and using Luhmann’s social system theory, it explores the causes of the crisis and the formation of a Community-Based Tourism (CBT) communication system. Findings reveal that environmental degradation stems from farmers’ vulnerability and tourism complexity. Effective CBT development requires inclusive participation, fair income distribution, and alignment with the Borobudur image. The study concludes that balancing tourism growth with environmental and social justice is essential, and an inclusive communication system can enhance community involvement and reduce the adverse impacts of tourism.